2021
DOI: 10.1021/acs.jpcc.1c02423
|View full text |Cite
|
Sign up to set email alerts
|

Point Defects Modeling Explains Multiple Sulfur Species in Sulfur-Doped Na4(Al3Si3O12)Cl Sodalite

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Recently, Stoliaroff et al have suggested that high concentrations of chlorine vacancies can be created by F-center point defects using DFT modeling 62 . It was found that ground and excited states of the singly occupied molecular orbital and the triply degenerate lowest unoccupied molecular orbital for the F-center 63 .…”
Section: Electronic Propertiesmentioning
confidence: 99%
“…Recently, Stoliaroff et al have suggested that high concentrations of chlorine vacancies can be created by F-center point defects using DFT modeling 62 . It was found that ground and excited states of the singly occupied molecular orbital and the triply degenerate lowest unoccupied molecular orbital for the F-center 63 .…”
Section: Electronic Propertiesmentioning
confidence: 99%
“…Finally, it must be pointed out that at 𝜇 𝐸 𝐹 ~ 5 eV (the expected position of the Fermi level for KCl:S), four defects exhibit so low formation enthalpies that they are likely to be formed: VK, VCl, SCl and S2Cl. Their estimated computed concentrations for KCl grown at 1000K in S-rich atmosphere and quenched to room temperature are given in Table 1 (details on the computations of concentrations can be found has already been details in several publications 24,25 ). In these conditions, it can be seen that intrinsic vacancies will be the most common types of defects but SCl and (S2)Cl are in significant concentration.…”
Section: Sulfur Impurities In Kclmentioning
confidence: 99%
“…Finally, it must be pointed out that at μ E F ∼ 5 eV (the expected position of the Fermi level for KCl:S), four defects exhibit very low formation enthalpies that they are likely to be formed: V K , V Cl , S Cl , and S 2Cl . Their estimated computed concentrations for KCl grown at 1000 K in the S-rich atmosphere and after being quenched to room temperature are given in Table (details on the computations of concentrations can be found in several publications , ).…”
Section: Defect Formation Enthalpymentioning
confidence: 99%
See 1 more Smart Citation
“…Due to composition and crystal structure similarities between the three minerals considered in this article, it has been assumed that this photochromic mechanism is the same for all of them. However, analysis of the oxidation states of sulfur in these minerals typically reveals a large variety of sulfur-based species ( 19 , 20 ), and we cannot rule out the possibility that the F-center can be generated from another sulfur impurity than S 2 2− . This will be investigated in the following by considering other sulfur impurities.…”
mentioning
confidence: 93%